Valorisation Of Poultry Byproducts for Complementary Pet Food Production: A Circular Economy Approach - Venkateswarlu, J; P Gadekar, Yogesh; Ambedkar, Y R; Nagamallika, E; Prasada Rao, T (Journal of Meat Science, 2026)
The pet food market is rapidly expanding as pet owners increasingly seek high-quality diets for their dogs. The pet food industry utilizes approximately 23% of the rendered poultry proteins produced annually. Poultry byproduct meal (PBM) is derived from poultry slaughter waste, including heads, viscera, feathers, and other byproducts. The fat in PBM is rendered and repurposed. For the production of extruded dry pet food for adult dogs, a formulation was developed. This mixture is processed through a twin-screw extruder at 120°C, resulting in extruded dry pet food. The pet food was analysed for various parameters like water activity of 0.41 and in-vitro digestibility of 78.24%. The calcium, phosphorus, iron, Zinc, magnesium, and manganese levels were recorded at 0.95%, 0.59%, 610mg, 51mg, 0.0046mg, 20mg/kg, respectively. The proximate composition of the pet food indicated moisture content at 1.54%, protein at 23.8%, crude fat at 8.7%, crude fibre at 2.0%, and total ash at 0.98%. Colour parameters revealed a lightness (L*) of 28.66, redness (a*) of 8.20, and yellowness (b*) of 17.20 and the amino acid profile was analysed.